Members' perceptions of the dynamics forest farmer groups at special purpose forest area (KHDTK) Gunung Bromo - Wulandari, Almira Mutiara; Widiyanto; Anantanyu, Sapja (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The goal of national development is to realize a sustainable agricultural system that is destructive without ecosystems and maintains the condition of the forest environment. One approach that the government can take to help agricultural development is through a group approach. The differences in the characteristics of forest plantations and agriculture make the activities of forest farmer groups an opportunity to maximize natural resources. The basic method used is quantitative with survey techniques. The research location is in villages or sub-districts around the Gunung Bromo Special Purpose Forest Area / Kawasan Hutan dengan Tujuan Khusus (KHDTK) Gunung Bromo. KHDTK Gunung Bromo, namely the villages of Sewurejo, Gedong and Delingan in Karanganyar District, Karanganyar Regency, Central Java, Indonesia. The research sample used proportional random sampling technique. The samples taken were 58 respondents who were members of agricultural forest groups covering three villages. Data collection was carried out using questionnaires, interviews and documentation. Data analysis used the Spearman Rank Test. The research results show that the perception of members at KHDTK Gunung Bromo is in the positive category.